The relevance of knowledge and information management for innovation generation - da Silva, Elaine [UNESP]; Valentim, Marta Lígia Pomim [UNESP] (IGI Global, 2024)
Recognizing that the sharing of information and knowledge is a preponderant factor for the generation of innovation and that innovative performance in a nation depends on the ability of innovation agents to share information and knowledge focusing on innovation, this chapter aims to highlight why and how information management (IG) and knowledge management (KM) processes constitute valuable subsidies for the generation of innovation. In addition, it presents and analyzes organizations whose purpose is the management of knowledge and information, such as archives, libraries, information/documentation centers, and museums seeking to show that these organizations have the potential to play an important role in the context of innovation systems.